Shifting Gears: An Exploratory Study of Factors Impacting the Well-being of Retired Faith-based Ministers in Australia and New Zealand - Erasmus, Bernadene (Journal of religion, spirituality & aging, 2022)
The rising tide of aged citizens globally suggests a compelling argument for increased understanding of factors impacting aging and retirement. Extended insight into the well-being of lesser studied groups offer suggestions to potentially enhance future planning for aging citizens. A study exploring the experience of clergy in Australia and New Zealand suggests a substantive theory on retirement in this context. A grounded study approach was adopted as best fit. Semi-structured interviews were conducted with 42 retired clergy and their wives. Findings suggest the underpinning role of spirituality in the primary elements of; choice, flexibility and connectivity as factors impacting the well-being of faith-based retirees in this context.